Absorption of ultrasonic waves in aqueous solutions of α-cyclodextrin with alkylpyridinium or alkyltrimethylammonium bromides - BALCERZAK, A.; PŁOWIEC, R.; JUSZKIEWICZ, A. (Archives of Acoustics, 1998)
Measurements of the absorption coefficient, α/f2, of aqueous solutions of α-cyclodextrin with alkylpyridinium bromides CnH2n+1C5H4NBr or alkyltrimethylammonium bromides CnH2n+1N(CH3)3Br (n = 8, 10, 12), were carried out at 15, 25, 35 and 45°C in the concentration range 0.01 M to 0.04 M and frequency range 1 MHz to 150 MHz. The occurrence of two ultrasonic relaxation processes has been noted. The obtained results have been compared with data published previously for sodium alkyl sulfates.